(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Sugarcane is a renewable, natural agricultural resource because it provides sugar, besides biofuel, fibre, fertilizer and myriad of byproductsco-products with ecological sustainability’. The world demand for sugar is primarily derived from sugar cane. Sugar cane accounts for eighty per cent of sugar produced and the rest is made from sugar beets. Sugarcane predominantly grows in the tropical and subtropical regions, and sugar beet predominantly grows in colder temperate regions of the world. A few merchants began to trade in sugar - a luxury and an expensive spice until the 18th century. Before the 18th century, cultivation of sugarcane was largely confined to India. Sugarcane plantations, like cotton farms, are a major driver of large human migrations in the 19th and early 2O century.